Prevalence and patterns of facemask use in marketplaces in Addis Ababa: Implications for targeted SARS-CoV-2 risk communication - Amanuel Gebru Woldearegay (Cogent Social Sciences, 2022)
COVID-19 is arguably the most challenging global pandemic ever, but it is considered preventable. A number of prevention strategies have been popularized through risk communication strategies. These have included facemask wearing, which has included a lot of attention that has covered concerns including whether people wear them and how correctly. The study intended to measure the facemask-wearing practices of Addis Ababa residents in street markets as well as the factors predicting facemask use. Based on WHO protocols, the categories of facemask use included full compliance, partial use, and no facemask use across gender and age categories. Visual-epidemiology methods were used in the objective observation of facemask–wearing. Data were collected as video recordings of facemask wearing behaviors among people in street markets in a randomly selected borough of Addis Ababa by a trained cameraman over 3 days and analyzed by two coders. Individuals observed were assessed for full compliance, partial compliance, and no compliance. Coders A and B rated 316 observations individually, respectively. Inter-rater agreement averaged 91%. The observations were further analyzed using multinomial logistic regression methods. The results showed that 400 (63.3%) did not wear a facemask at all, 137 (21.7%) used facemasks correctly, and the remaining 95 (15%) used them partially. About 69% of males and 52% of females failed to use any facemask. Failure to use facemasks was highest among teens (93.6%). Further, parameter estimates showed age and gender were significant predictors of facemask use. Study limitations and implications for targeted risk communication are discussed.